Determination of Marketing Performance: Display Media, Affiliate Marketing and Social Media (Literature Review) - Nursal, M. Fadhli; Hadita, Hadita; Marundha, Amor; Komariah, Neng Siti (International Journal of Advanced Multidisciplinary, 2022)
The Literature Review article on Marketing Performance Determination: Display Media, Affiliate Marketing and Social Media is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Media Display has an effect on Marketing Performance; 2) Affiliate Marketing has an effect on Marketing Performance; and 3) Social Media has an effect on Marketing Performance. Apart from these 3 exogenous variables that affect the endogenous variable of Marketing Performance, there are many other factors including Search Engine Advertising, Search Engine Optimization and E-mail Marketing variables.